Analysis of maternal mortality in Piauí before and during the Covid-19 pandemic in the years 2019 to 2020 (Research, Society and Development, 2022)
Objectives: To assess the maternal mortality rate during the COVID-19 pandemic and describe the main reasons for maternal mortality. Methods: This scientific work was carried out according to the DATASUS (Department of Health Information) database, where the study participants were women who were victims of maternal mortality due to the COVID-19 pandemic. The incidence of maternal deaths in the period from 2019 to 2020 in Piauí, the sociodemographic profile, and the municipalities in Piauí with the highest incidence of maternal death as a result of the pandemic were included in the study. Results and Discussion: It was possible to analyze that in 2020 where there was less damage in relation to the coronavirus, the maternal mortality rate decreased by 30% compared to 2018 which was only 3%. Conclusion: it is expected that with the increase in studies related to maternal mortality, it will be possible to identify the real risk that these women faced and still face with regard to COVID-19. In addition, it is still worth mentioning in future studies, the impacts suffered be it emotional, physical or social by pregnant women and in the puerperium.